2010
DOI: 10.1002/isaf.318
|View full text |Cite
|
Sign up to set email alerts
|

The impact of website design on the perceived credibility of internet financial reporting

Abstract: Marketing and information systems research show that surface features of a website can induce credibility effects. We conduct an experiment to examine the question of credibility effects induced by the surface features of webbased fi nancial reporting. We predict that participants will perceive fi nancial data from sites with surface fl aws (poor style and incompleteness) to be of lower credibility. Consistent with our expectations, we fi nd that surface features can signifi cantly affect users' perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition to the various things above, business organizations utilize the www system to publish information related to investors or potential investors. The results of the general shareholders meeting, management discussions and analysis, and financial statements have been accessed through the www system on the internet (Allport & Pendley, 2010; Kesavan et al, 2021). The need for internet‐based financial reporting has been realized since 1994 by AICPA due to the emergence of the need for a financial reporting system that is flexible, accessible, fast, and reliable, while the paper‐based reporting system has been considered unable to meet these needs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition to the various things above, business organizations utilize the www system to publish information related to investors or potential investors. The results of the general shareholders meeting, management discussions and analysis, and financial statements have been accessed through the www system on the internet (Allport & Pendley, 2010; Kesavan et al, 2021). The need for internet‐based financial reporting has been realized since 1994 by AICPA due to the emergence of the need for a financial reporting system that is flexible, accessible, fast, and reliable, while the paper‐based reporting system has been considered unable to meet these needs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The fast expansion of the Internet provides firms with new channels of communication with investors (Siahaan et al, 2021). As such, disclosure of information on the firm's website will lessen ambiguity over the company's prospects (Allport and Pendley, 2010;Khan, 2007;Raman et al, 2003;Sabrina et al, 2019;Suciani et al, 2020). Studies imply that investors prefer to invest in their home markets due to knowledge asymmetries between local and overseas investors and behavioral biases generated by unfamiliarity with other markets (Amiram, 2012), highlighting the importance and relevance of corporate reporting to a broader audience.…”
Section: *Inmentioning
confidence: 99%
“…Visual aids make the message seem more trustworthy (Qiu and Benbasat, 2005). Prior studies have found that the perceived visual attractiveness of a website can increase the perceived usefulness (Van Der Heijden, 2003) and credibility (Allport and Pendley, 2010) of the information presented on the website. We assume that if a picture supports the rumor, or if the social media platform or website is pleasing to the receiver's eye, the rumor will be more convincing to the receiver.…”
Section: Attractivenessmentioning
confidence: 99%